2006
DOI: 10.2165/00148581-200608050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapy of Inflammatory Bowel Disease in Children

Abstract: Ulcerative colitis (UC) and Crohn disease (CD) are chronic intestinal inflammatory diseases that can present as bloody diarrhea, abdominal pain, and malnutrition. Collectively, these disorders are referred to as inflammatory bowel disease (IBD). All patients with IBD share a common pathophysiology. However, there are a number of developmental, psychosocial, and physiologic issues that are unique to the approximate, equals 20% of patients that present during childhood or adolescence. These include the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 203 publications
0
77
0
4
Order By: Relevance
“…Therefore, rational and effective nutrition support will be conductive to malnutrition cancer patients. It has been previously reported that the function of small intestine usually began to recover within 6~12 h after operations (8), indicating the possibility of initiating EN support. Early postoperative EN rather than parenteral nutrition is advocated by researchers when intestines can normally work (9), which thus allows the wide application of EN support in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, rational and effective nutrition support will be conductive to malnutrition cancer patients. It has been previously reported that the function of small intestine usually began to recover within 6~12 h after operations (8), indicating the possibility of initiating EN support. Early postoperative EN rather than parenteral nutrition is advocated by researchers when intestines can normally work (9), which thus allows the wide application of EN support in clinical practice.…”
Section: Discussionmentioning
confidence: 89%
“…Thus far, several uncontrolled (9,14,15,17,19) and two placebo-controlled studies (13,18) have demonstrated that tacrolimus can induce remission in both adults (9, 13-15, 17, 18) and children (19). Another calcineurin inhibitor, CsA, is also highly active (60% to 80%) in patients with UC whose disease fails to respond to intravenous corticosteroid therapy (20). However, CsA has not been shown to improve long-term prognoses because it does not appear to be able to prevent relapse or colectomy once administration is stopped (6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CsA is known to be associated with many adverse effects, such as infections, renal dysfunction, hypertension and neurological toxicity (6). Although similar adverse events, including tremors, hyperglycemia, nephrotoxicity and infection, are observed in association with tacrolimus therapy, these effects are generally mild and reversible (19)(20)(21); thus, tacrolimus can be safely administered on a long-term basis. Yamamoto et al investigated the efficacy of tacrolimus as maintenance therapy for patients with refractory UC and suggested that the administration of tacrolimus with low trough levels (5 to 10 ng/mL) as maintenance therapy may represent an alternative therapy for UC patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…However, the anti-colitis effect of SMS is not understood. UC is a chronic intestinal inflammation resulting in symptoms that include abdominal pain, weight loss and bloody diarrhea (Ardizzone and Bianchi, 2005;Rufo and Bousvaros, 2006;Sato et al, 2007).…”
Section: Discussionmentioning
confidence: 99%